Adapting Learning Activities for Teaching Know-How in Adaptive Course Generation System - Nguyen, Viet Anh (ĐHCN, 2016)
In our previous work, we have built an adaptive course generation system (ACGS) [1] to adapt a learning path for learning goals. In this paper we describe learning activity is represented in the learner model and domain model to teach learners how to get through course content based on learner’s knowledge. Therefore, our model aim is to develop Bayesian Network learner model to manage overlay knowledge model and adapt learning activities based on a task model. In addition, an implementation of this model with the course topic about computer science domain for third year students is also described.